Microbiology Profile in Women With Pelvic Inflammatory Disease in Relation to IUD Use - S. Olofsson; L. Berglund; J. Kroica; G. Lazdane; V. Odlind; I. Viberga (Hindawi Limited, 2005)
Objective. To study the microbial characteristics of patients with pelvic inflammatory disease (PID) and the possible impact of an intrauterine device (IUD) on the microbial environment in women presenting with PID.